Irish writers and the British periodical press 1880-1900 - MORONEY, NORA (Trinity College Dublin. School of English. Discipline of English, 2019)
This project assesses the extent and significance of Irish contributions to the British periodical press of the 1880s and 1890s. It examines the cultural and historical context of some fifteen writers, situating them in a transnational framework of periodical discourse during a period when the political and colonial entanglements of Ireland with Empire were bringing pressure to bear on exclusivist conceptions of Irish and British identity. This research specifically focuses on literary journalism in Britain as opposed to the newspaper press, positing the writers under consideration as elite opinion-formers who took a central part in, and to various degrees shaped and represented, the intellectual culture of late Victorian Britain. The thesis comprises five chapters. Three of these focus on individual journal titles 'The New Review', 'Nineteenth Century' and 'Fortnightly Review' while the remaining two present single-author case studies on W.E.H. Lecky and Emily Lawless. Drawing on the tools and methodology of periodical criticism, it situates each article within its specific material and cultural context and utilises a range of primary sources alongside textual and historical analysis to discern any underlying ideology in relation to the journals. By focusing on both periodicals and case studies the project aims to come to a deeper understanding of the significance of certain types of press discourse, not only in each writer's conception of their work as an essayist but in the many negotiations of national identity in the press at the time. This is explored in relation to (among other things): the Home Rule crisis, questions of censorship and cultural authority, European literary trends and British Liberal ideology. Authors such as George Moore and J.P. Mahaffy are also examined in the context of growing professionalisation and academic disciplinisation, and the pressures that these developments exerted on both the periodicals and the Victorian 'man of letters' tradition. They are appraised alongside fiction writers such as W.B. Yeats, Sarah Grand and Standish O'Grady and the political interventions of Justin McCarthy and Horace Plunkett. I seek to demonstrate how, despite the growing influence of cultural nationalist rhetoric, the 1880s and 1890s provided a fertile and encouraging space for Irish writers to articulate their various diverse interests within some of the most influential British cultural organs of the day.
APPROVED
Keywords: Irish literature; Publishing history; Periodical studies; Transnationalism